161 Low haptoglobin level in lupus without hemolysis. (April 2019) - Timlin, Homa
Abstract : Background: Low haptoglobin indicates hemolysis in lupus patients. We present a lupus patient who was found to have low haptoglobin levels in the absence of other evidence of hemolysis. Methods: Chart review. Results: A 44-year-old Caucasian woman was diagnosed with lupus about 11 years ago, characterized by positive ANA, anti-dsDNA, anticardiolipin antibodies, anti-beta-2 glycoprotein, Direct Coombs, hypocomplementemia, alopecia, arthralgia, arthritis, photosensitive skin rash, serositis, mucosal ulcer, and livedo. She was treated with hydroxychloroquine, steroids, and Imuran. During her first visit in our center, she was found to have mild alopecia and subtle synovitis of 2 small joints. She was taking hydroxychloroquine 400 mg. The hematocrit was 34 (up from 30–31, 3 months prior to the visit and 3 months after the visit), haptoglobin 41 mg/dL (normal 43–212 mg/dL), absolute reticulocyte count of 73 000/mm 3 (normal 20000–80000), negative Direct Coombs, low positive anti-dsDNA of 15 (negative <4 IU/ml), low C3 of 72 mg/dL (normal 90–180), normal C4 of 17 mg/dL (normal 16–47), platelet counts of 147000 (140000–400000/uL), normal WBC (3 months prior to the visit and 3 months after the visit), normal urine protein creatinine ratio of 99 mg/g creatinine (normal 21–161), normal liver function test (one month prior and 3 months after the visit), and CRP was normal (<0.1 mg/dl). Conclusions: Further research is needed to detect anti-haptoglobin antibodies in lupus patients and elucidate the mechanism underlying these findings. Funding Source(s): Non.